CD14 Polymorphism Is Not Associated with SARS-CoV-2 Infection in Central European Population - Hubáček, Jaroslav; Philipp, Tom; Májek, Ondřej; Dlouhá, Dana; Adámková, Věra; Dušek, Ladislav (Folia biologica, 2023)
A 2021 in silico study highlighted an association between the CD14 polymorphism rs2569190 and increased susceptibility to SARS-CoV-2, which causes coronavirus disease 2019 (COVID-19). The aim of our study was to confirm this finding. We analysed the CD14 polymorphism (C→T; rs2569190) in 516 individuals who tested positive for SARS-CoV-2, with differing disease severity (164 asymptomatic, 245 symptomatic, and 107 hospitalized). We then compared these patients with a sample from the general population consisting of 3,037 individuals using a case-control study design. In comparison with carriers of the C allele, TT homozygotes accounted for 21.7 % of controls and 20.5 % in SARS-CoV-2-positive individuals (P = 0.48; OR; 95 % CI - 0.92; 0.73-1.16). No significant differences in the distribution of genotypes were found when considering co-dominant and recessive genetic models or various between-group comparisons. The CD14 polymorphism is unlikely to be an important predictor of COVID-19 in the Caucasian population in Central Europe.
Keywords: genetická predispozice k nemoci; Humans; lidé; SARS-CoV-2; Polymorphism, Single Nucleotide; Case-Control Studies; studie případů a kontrol; COVID-19; Genetic Predisposition to Disease; jednonukleotidový polymorfismus